Implementation of Low Earth Orbit Satellite Constellation Design - Puteh, Muhammad Haikal; Setiawan, Dhoni Putra; Edwar, Edwar (eProceedings of Engineering, 2025)
The increasing utilization of Low Earth Orbit (LEO) satellites necessitates accessible and accurate design tools that can serve as alternatives to expensive professional software. This project addresses this need by developing a comprehensive web-based application for LEO satellite orbit design. The application integrates several key functionalities, including orbit propagation, constellation design for both Train and Walker-Delta configurations, coverage analysis, and link budget calculations, all enhanced with interactive 2D and 3D visualizations. The application underwent rigorous validation against theoretical calculations and NASA's General Mission Analysis Tool (GMAT), confirming high accuracy across all modules. The orbit propagation module demonstrated an error of less than 0.78 km over a one-hour simulation, with a root mean square error (RMSE) of 31.8 km when compared to GMAT's numerical integrator. Constellation placement for both Train and Walker-Delta configurations showed zero positional error. Coverage calculations were accurate to within 0.05 km at an altitude of 2,000 km. Furthermore, the link budget analysis achieved perfect correspondence with manual calculations, showing a 0.00 dB difference and yielding an uplink margin of 31.87 dB and a downlink margin of 18.76 dB. Predictions for ground station access precisely matched theoretical schedules, with 11 passes in 24 hours and an average duration of 8.55 minutes. User interface testing resulted in a 100% success rate. This application successfully bridges the gap between complex professional software and educational needs by providing a validated, reliable, and accessible tool for the preliminary design of LEO satellite missions. It meets all project objectives by combining high computational accuracy, comprehensive features, and cost-free web-based accessibility, thereby making satellite orbit design more approachable for educational purposes and initial technical assessments. Keywords: LEO, Satellite Orbit Design, Constellation, Orbit Simulation, Link Budget, Web Application